PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL ANTARA PEKERJA DAN PENGUSAHA - Wirayuda Kusuma, I Made; Wirasila, A. A. Ngurah (Kertha Semaya : Journal Ilmu Hukum, 2013)
The process of making the agreement made with a short practice, because it usesstandard contract forms, so that in the process of making the agreement does not gothrough the stages of pre-contract, as is usually preceded by the process of negotiationbetween the workers and employers, and also agreements made under the arms. Althoughagreements made in the form of standard contract and under the arms, but the agreement isstill subject to the attempted reference and the provisions contained in article 1320 CivilCode and article 52 paragraph 1 of Law of the Republic of Indonesia Nomor13 of 2003which is the legal basis of the employment agreement.Settlement of industrial disputes between workers and employers, has been cited inthe letter of agreement which is about legal consequences imposed on employees whoviolate the terms agreed in the employment agreement that if the employer or the employeeterminate employment agreement for a specified time before the time expires, the partiesshall terminate the employment agreement to pay compensation to the other party at thetime or wages to the workers should be done, unless the employment relationshipbreakdowns or faults because of severe labor force.
Keywords: Industrial Disputes, Workers, Employers